Continuing Medical Education Questions: April 2019. (April 2019) - Ho, Edith Y.
Abstract : To receive CME/MOC credit for this activity, please go to: http://acgjournalcme.gi.org/ Article Title: Diagnosis and Treatment of Rumination Syndrome: A Critical Review